'Schizophrenic' behavior of poly (N-isopropylacrylamide)-b-poly (2-vinylpyridine) in aqueous solutions. (February 2018) - Liu, Dong; Wei, Chengsha; Yan, Guanyun; Sun, Guangai
Abstract: A series of well-defined double hydrophilic block copolymers Poly ( N -isopropylacrylamide)- b -poly (2-vinylpyridine) (PNIPAM38 - b -P2VP43 ) were synthesized. The 'schizophrenic' behavior and the aggregation process of PNIPAM- b -P2VP in response to temperature and pH in dilute aqueous solution were tested via transmittance measurements, dynamic light scattering (DLS), and small-angle neutron scattering (SANS). The results revealed that: i) both PNIPAM-core and P2VP-core micelles can be induced from an intermediate unimers state via the adjustment of temperature and pH; ii) The lower critical solution temperature (LCST) of PNIPAM homopolymers is narrowly in the range of 31–34 °C, while PNIPAM- b -P2VP diblock copolymers at pH = 7 and 2 have broad LCSTs of 25–40 °C and 41-50 °C, respectively; iii) SANS results show that only the PNIPAM- b -P2VP solution at pH = 7 and 50 °C (both blocks are hydrophobic) has a sphere form factor with diameter of about 110 nm. Highlights: Well-defined double hydrophilic block copolymers PNIPAM38 - b -P2VP43 were synthesized. The LCST of PNIPAM block is largely affected by the P2VP block and its conformation. The 'schizophrenic' behavior of PNIPAM- b -P2VP in response to temperature and pH were investigated. Both PNIPAM-core and P2VP-core micelles can be induced via the adjustment of temperature and pH. SANS results show that PNIPAM- b -P2VP solution at pH = 7 and 50 °C has a sphere form factor.